Surface Functionalised Parenteral Nanoemulsions for Active and Homotypic Targeting to Melanoma - Federica Foglietta; Annalisa Bozza; Chiara Ferraris; Luigi Cangemi; Valentina Bordano; Loredana Serpe; Katia Martina; Loretta Lazzarato; Stefania Pizzimenti; Margherita Grattarola; Marie Angele Cucci; Chiara Dianzani; et al. (MDPI AG, 2023)
Despite recent progressions in cancer genomic and immunotherapies, advanced melanoma still represents a life threat, pushing to optimise new targeted nanotechnology approaches for specific drug delivery to the tumour. To this aim, owing to their biocompatibility and favourable technological features, injectable lipid nanoemulsions were functionalised with proteins owing to two alternative approaches: transferrin was chemically grafted for active targeting, while cancer cell membrane fragments wrapping was used for homotypic targeting. In both cases, protein functionalisation was successfully achieved. Targeting efficiency was preliminarily evaluated using flow cytometry internalisation studies in two-dimensional cellular models, after fluorescence labelling of formulations with 6-coumarin. The uptake of cell-membrane-fragment-wrapped nanoemulsions was higher compared to uncoated nanoemulsions. Instead, the effect of transferrin grafting was less evident in serum-enriched medium, since such ligand probably undergoes competition with the endogenous protein. Moreover, a more pronounced internalisation was achieved when a pegylated heterodimer was employed for conjugation (p < 0.05).